Entre a coerção e a negociação: as relações entre a Rede Globo e a Censura Federal (1969-1983) - Silva, Thiago de Sales (2023)
The present thesis examines the intricate relationships maintained between TV Globo and the Federal Censorship during the brazilian military dictatorship, with the propose of comprehending the TV channel's ambivalent strategies in response to interventions by the prevailing censoring apparatus, as well as the diverse stances of the regime in this dynamic. By setting a temporal cut spanning from the late 1960s to the early 1980s, it allowed us to go through different phases of policies and repressive actions directed towards public entertainment, particularly television programming, in the areas of the Division of Censorship of Public Entertainment (DCDP), the intelligence community, and the Superior Censorship Council (CSC). For that, we look at sources such as: censorship processes of soap opera like "Véu de Noiva" (1969), "Irmãos Coragem" (1970), "O Homem que deve Morrer" (1971), "Selva de Pedra" (1972), "Roque Santeiro" (1975), and "Despedida de Casado" (1977); censorship legislation; comunications, dossiers and reports produced by surveillance agencies; autobiographical documents of individuals who were part of the TV Globo's staff; and newspapers. Between specific bans, formal flexibilities, and strict prohibitions, we explore the constitution and limits of the negotiation space established in this process.